Value Orientations and Job Search Strategies of St. Petersburg Residents in the Context of the COVID-19 Crisis - Anastasia Alexandrova; Maya Rusakova; Sergey Tkach (Journal of Economic Sociology, 2024)
The article examines the relationship between value orientations and job search strategies of the unemployed in St. Petersburg. The authors rely on the existential understanding of attitudes as constructed by people’s actions, pushing them to form certain value orientations. Orientations influence people’s vision of the state of the labor market and their chances in it. The empirical database included questionnaires from 1,857 people registered as unemployed with the St. Petersburg Employment Service. The main tool of analysis was cluster analysis using the K-means method. The resulting clusters were assessed using the silhouette measure and the DavisBaldwin index. The statistical significance of differences between clusters was determined using the KruskalWallis test. Three stable clusters were identified: pessimists with a predominant orientation of reliance on others (29.2% of respondents), optimists with a predominant reliance on themselves (29.7% of respondents), and optimists with moderate orientationsrelying on themselves and others (41% of respondents). It is shown that the prevalence of value orientations of optimism (the first cluster), as well as value orientations of pessimism (the second cluster), makes people less active in using support measures in the labor market and also reduces their willingness to undergo retraining. The prevalence of value attitudes of optimism in combination with reliance on themselves, at the same time, contributes to greater cooperation with employment centers. Also, respondents are more interested in assistance in employment than in professional retraining. The results obtained make a significant contribution to the discussion about the prospects of the existential approach in labor market research, and the conclusions can form the basis for individualized programs to help job seekers that take into account the value orientations of citizens.